Regulation of Notch1 Signaling by Nrf2: Implications for Tissue Regeneration - Wakabayashi, Nobunao (2010)
The Keap1-Nrf2-ARE signaling pathway evokes an adaptive response for cell survival following endogenous (for example, inflammation) and exogenous (for example, carcinogens) stresses. Keap1 inhibits the transcriptional activation activity of Nrf2 in unstressed cells by facilitating its degradation. Through transcriptional analyses in Keap1- or Nrf2-disrupted mice, we identified interactions with the Notch1 signaling pathway. We found a functional antioxidant response element (ARE) recognized by Nrf2 in the promoter of Notch1. Notch1 regulates processes such as proliferation and cell fate decisions. We report a functional role for this cross talk between the two pathways and show that disruption of Nrf2 impeded liver regeneration following partial hepatectomy and was rescued by re-establishment of Notch1 signaling.